The significant of a wayfinding plan for Jong’s crocodile farm and zoo as a factor to add customer satisfaction / Alex Anderian Geling - Geling, Alex Anderian (Faculty of Art and Design, 2013)
The problem of this research is to verify the wayfindings issue at Jong’s crocodile Farm and zoo. The main purpose of the study is to examine whether wayfinding system is important to add customer visits and satisfaction. Also, to support this study, the literature review establishes a basis of environmental design consists of definition, theory and signage system according to previous scholar related to wayfinding plan. Objective and research methodology: Data for this research was collected through survey. Survey divided into two parts, which is questionnaire and interview. A total of 35 visitors at Jong’s crocodile farm choose randomly. The random respondent was selected from Sarawak, Sabah, peninsular Malaysia and tourist from others country. Each question consists of two parts, part A is a demographic question and part B is a set of question based on visitor knowledge and opinion. Also, an interview with the Jong’s staff also is part of the data collection. Three important questions have been asked in order to know the Jong’s staff’s opinion towards the issue related. This interview research required an experience worker who work more than 3-4 years who familiar with the zoo environment. The conclusions are based on findings through primary data and secondary data.